A novel Bluetooth low energy based system for spatial exploration in smart cities. (1st July 2017) - Boukhechba, Mehdi; Bouzouane, Abdenour; Gaboury, Sébastien; Gouin-Vallerand, Charles; Giroux, Sylvain; Bouchard, Bruno
Highlights: Smart spatial recognition service in smart cities. The system relies on nomadic data collection and sharing using Bluetooth 4.0. The system operates without predefined geo-databases or internet connectivity. Tests have been conducted using both real and simulated data. Results show that the system improves the user's urban explorations. Abstract: Smart Cities are employing information and communication technologies in the quest for sustainable economic development and the fostering of new forms of collective life. They facilitate connections between citizens and organizations that are of paramount importance for their long-term sustainability. As cities become more complex and their communities more dispersed, questions such as 'where can I find …' are increasingly pertinent. In this paper, we introduce NomaBlue, a new vision of spatial recognition in smart cities, the proposed system is based on an intelligent nomadic data collection and users' collaboration using smart Bluetooth technology. We demonstrate using two case-studies that our approach is capable of proposing an efficient spatial recognition service while supporting a range of users' constraints, our system is disconnected from the internet, it can operate in any indoor/outdoor area, it doesn't require pre-defined geographic databases and uses a new concept of nomadic data collection and sharing to speed-up the circulating information in smart cities.